Restoring a glacier‐fed river: Past and present morphodynamics of a degraded channel in the Italian Alps. Issue 12 (21st July 2020) - Scorpio, Vittoria; Andreoli, Andrea; Zaramella, Mattia; Moritsch, Sara; Theule, Joshua; Dell'Agnese, Andrea; Muhar, Susanne; Borga, Marco; Bertoldi, Walter; Comiti, Francesco
Abstract: The present study explores the evolutionary trajectory of the glacier‐fed Mareit River (South Tyrol, Italian Alps), where a large restoration programme was implemented in 2008–2009. River corridor changes before and after the restoration works were assessed using historical maps, recent field observations, topographic surveys and topographic differencing. Trends of anthropic (forest cover, channel works, gravel mining) and natural (glacial cover, precipitation, flow regime) factors controlling channel morphology – at both catchment and reach scales – were reconstructed. From the mid‐19th century, the evolutionary trajectory of the Mareit River followed a degradational trend, characterized by channel narrowing, bed incision and planform simplification. Direct, in‐channel human alterations – mainly in the form of bank protections (in the late 19th century), gravel mining (mostly in the 1970s) and grade‐control works (since the 1980s) – dominated the historical adjustments before the restoration. In 2008–2009, a segment of the Mareit was restored by widening the channel, partly removing the check‐dams and shaping a braided pattern within a laterally constrained corridor. Post‐work monitoring shows that the restoration improved both the morphological quality and the geomorphic diversity. At present, the channel is subject to narrowing and slight bed level incision, with islands and floodplains progressively expanding at the expenses of the active channel. This trend is likely to continue in the next decades based on the expected future flow regime, and indeed the Mareit River seems to be attaining a 'miniaturized' version of the anabranching pattern of the mid‐19th century. Overall, this restoration approach and the associated evolutionary trajectory is considered positive, because it leads to a complex mosaic of geomorphic units, dynamically self‐adjusting to the time‐varying driving variables. The formation of a morphodynamically active corridor, while keeping artificially non‐erodible boundaries, represents an optimal strategy to integrate ecological improvements with flood risk mitigation in the densely populated Alpine valleys. © 2020 John Wiley & Sons, Ltd. Abstract : The Mareit River underwent a severe channel degradation in the second half of the 20th century, followed by an important restoration intervetion in 2008‐2009. The graphic abstract illustrates the temporal changes in channel and floodplain widths, planform pattern and morphological quality.